Homeroom Management Model to Improve Pancasila Learner Profile - Syofianti Engreini; Sahrun Nisa; Whyosi Septrizola; Ade Herdian Putra (JETL (Journal of Education, Teaching and Learning), 2025)
The homeroom teacher plays a crucial role as a parental substitute in strengthening students' character at school. One method of character reinforcement is through the implementation of the Pancasila Student Profile (P4). Effective and consistent management by the homeroom teacher is essential for this implementation. This study aims to develop a homeroom teacher management model to enhance the quality of strengthening the Pancasila Student Profile using the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The study addresses three main research questions: the characteristics of the homeroom teacher management model, its validity, and its practicality. Data collection instruments included observation sheets and questionnaires validated by experts. The product was validated by experts and tested at SDN 01 Koto Baru and SDN 13 Koto Baru. Qualitative data were gathered through surveys, and qualitative insights were obtained through observations, feedback, and written suggestions for improvement. Needs analysis results indicated deficiencies in the planning, organization, execution, and evaluation of activities by homeroom teachers. This research produced a validated instrument that is both valid and reliable. The practicality of the homeroom teacher management model to enhance the Pancasila Student Profile, and the management guide, was determined based on homeroom teachers' responses to the model's practicality and guidance. The study resulted in a homeroom teacher management model and a management guidebook to improve the quality of strengthening the Pancasila Student Profile. These findings are expected to significantly contribute to homeroom teachers in reinforcing students' character in alignment with the Pancasila Student Profile.